2021
DOI: 10.1371/journal.pone.0251072
|View full text |Cite
|
Sign up to set email alerts
|

Do women prefer caesarean sections? A qualitative evidence synthesis of their views and experiences

Abstract: Background Caesarean sections (CS) continue to increase worldwide. Multiple and complex factors are contributing to the increase, including non-clinical factors related to individual women, families and their interactions with health providers. This global qualitative evidence synthesis explores women’s preferences for mode of birth and factors underlying preferences for CS. Methods Systematic database searches (MEDLINE, EMBASE, CINAHL, PsycINFO) were conducted in December 2016 and updated in May 2019 and Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 80 publications
2
36
1
5
Order By: Relevance
“…Some hospitals had insufficient human resources and space limitations impeding constant support during birth. Evidence worldwide suggests fear of pain or lack of pain relief during labour as one of the primary factors underlying women preference for CS 7 15 36 37. Our formative research further reinforces the importance for women to have access to pain management strategies.…”
Section: Discussionsupporting
confidence: 66%
“…Some hospitals had insufficient human resources and space limitations impeding constant support during birth. Evidence worldwide suggests fear of pain or lack of pain relief during labour as one of the primary factors underlying women preference for CS 7 15 36 37. Our formative research further reinforces the importance for women to have access to pain management strategies.…”
Section: Discussionsupporting
confidence: 66%
“…In this line, mothers and practitioners could prefer a C-section for convenience reasons, and because it is apparently less painful and easier to plan. 26 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 Whether all these C-sections were indeed needed is debatable and deserves further evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to a recent review, only a minority of women from different countries and situations stated a preference for CS as a mode of delivery [ 44 ]. Many studies have even reported that women claimed they lacked autonomy over birth-related decisions, including the experiences of several women who said they had initially rejected the option of a CS, only to be eventually convinced to undergo CS by the doctor in charge at the time [ 45 50 ]. In Uruguay, it would be important to review and strengthen the implementation of existing clinical guidelines on the management of induction of labour and scheduling of caesarean delivery.…”
Section: Discussionmentioning
confidence: 99%